1990
DOI: 10.1152/jappl.1990.68.6.2312
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory response of spinal cord-lesioned subjects to electrically induced exercise

Abstract: Seven human spinal cord-lesioned subjects (SPL) underwent electrically induced muscle contractions (EMC) of the quadriceps and hamstring muscles for 10 min: 5 min control, 2 min with venous return from the legs occluded, and 3 min postocclusion. Group mean changes in CO2 output compared with rest were +107 +/- 30.6, +21 +/- 25.7, and +192 +/- 37.0 (SE) ml/min during preocclusion, occlusion, and postocclusion EMC, respectively. Mean arterial CO2 partial pressure (PaCO2) obtained from catheterized radial arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…However, other studies have shown that spinal cord trans-section does not abolish the hyperpnea of electrically induced muscle contraction in anesthetized animals (112,524,566). These experimental findings in animals are consistent with data on electrically induced contractions in humans with spinal cord injury (77,79) or in spinal cord-intact humans with epidural anesthesia to block peripheral afferents (160).…”
Section: Exercising Limbssupporting
confidence: 77%
“…However, other studies have shown that spinal cord trans-section does not abolish the hyperpnea of electrically induced muscle contraction in anesthetized animals (112,524,566). These experimental findings in animals are consistent with data on electrically induced contractions in humans with spinal cord injury (77,79) or in spinal cord-intact humans with epidural anesthesia to block peripheral afferents (160).…”
Section: Exercising Limbssupporting
confidence: 77%
“…An isocapnic hyperpnea is elicited during electrically induced contractions in paraplegic humans (3,19,55,57) These data appear inconsistent with mediation of the hyperpnea by spinal afferents, and since in spinal cord intact humans, theV E response to electrically induced and voluntary contractions does not differ, it would appear that a humoral mechanism mediates the hyperpnea. A major limitation of these studies is that the 50% to 100% increase in metabolic rate is within the physiologic variation that occurs at rest.…”
Section: Responses To Electrically Induced Muscle Contractionmentioning
confidence: 97%
“…This phase I response is observed during not only during voluntary and passive movement, but also during an electrically induced muscle contraction (Adams et al 1984;Brice et al 1988;Brown et al 1990;Miyamura l994). Nevertheless, many investigators have pursued the mechanisms of this phase I response, and their opinions as to its nature are still a matter of dispute.…”
Section: Introductionmentioning
confidence: 96%